Clinicopathological features and pathogenesis of hepatoid adenocarcinoma of the uterine cervix: a case report - Liu, Yuanyuan; Zhao, Renfeng (Frontiers in Oncology, 2025)
Hepatoid adenocarcinoma (HAC) is a specific extrahepatic adenocarcinoma with hepatocellular differentiation, often associated with elevated serum alpha-fetoprotein (AFP). HAC has been reported to occur in the stomach, ovaries, pancreas, uterus, and other sites. Despite the poor prognosis and few effective treatment options, timely and accurate histopathological diagnosis is essential to optimize clinical management for long-term survival. HAC of the uterine cervix is very rare and occurs mainly in postmenopausal women, and the first symptom is irregular vaginal bleeding in all cases, with elevated serum AFP values. HAC of the cervix is more prone to metastasis than ordinary cervical adenocarcinoma, and its prognosis is worse. The treatment plan still refers to the surgical treatment plan for cervical cancer, and radiotherapy or platinum-based combination chemotherapy is given after surgery. With the development of molecular pathology and next-generation sequencing technology, the pathogenesis of HAC is mainly related to hepatoid differentiation, gene mutation, and inflammatory stimulation. Only two cases have been reported in the literature, and one of the reasons for the lack of reports is the lack of knowledge of the clinical and pathological features of the disease; thus, improving the clinical understanding of HAC is crucial for better identifying patients with HAC of the cervix.